Moderating Role of Hisbah Institution on the Relationship of Religiosity and Islamic Culture to Islamic Work Ethics in Nigeria - Attahiru, Mustapha Sidi; Al-Aidaros, Al-Hasan; Yusof, Syarifah Binti Md (International Review of Management and Marketing, 2016)
An immoral act such as hoarding, interest dealing (riba), false swearing, inexact weight corrupt practices and market instability are some of the problems facing the Nigerian business environment. Despite all efforts by the Government and researchers, the problem persists. This is implied to the weaknesses in the existing conventional measures which are mainly based on western literature taken by the authorities on work ethics and also a lack of religiosity and good culture on the part of the stakeholders. To enhance business performance of Muslims in business, this study intends to employ a new framework based on Islamic approach and also develop a new relationship between religiosity, Islamic culture and Islamic work ethics with a moderating role of Hisbah institution. The proposed new framework will fill the gap in the field of Islamic work ethics in Nigeria and beyond. Keywords: Islamic work ethics, Religiosity, Islamic culture, Hisbah institution, Nigeria JEL Classifications: C610, C623, I23